A joint research agenda for climate action bridges behavioral sciences and urban planning - Felix Creutzig; Lucia A. Reisch (Communications Psychology, 2024)
We argue for systematically integrating behavioral sciences and urban planning to develop a joint agenda for research and planning practice. By viewing urban form as a critical choice architecture for making people’s choices more climate-friendly, this approach may unlock new pathways for higher liveability of cities.